2017
DOI: 10.3389/fphar.2017.00342
|View full text |Cite
|
Sign up to set email alerts
|

Peri- and Postoperative Treatment with the Interleukin-1 Receptor Antagonist Anakinra Is Safe in Patients Undergoing Renal Transplantation: Case Series and Review of the Literature

Abstract: In patients undergoing solid organ transplantation, the presence of an interleukin-1 (IL-1) driven disease may require the addition of IL-1 inhibiting drugs to the standard immunosuppressive regimen to protect against inflammation and negative graft outcome. Three patients undergoing renal transplantation were treated perioperatively with the interleukin-1 receptor antagonist anakinra. Kidney function increased rapidly in all three and the only complications seen were minor infections. In vitro studies report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Previous studies identified associations between levels of IL-1β and IL-1Ra in serum and urine and negative graft outcome; studies in experimental animals and observations in humans also substantiated a possible protective effect of blocking IL-1 after solid organ transplantation (reviewed in Mulders-Manders et al, 2017 ). New evidence suggests that in patients undergoing solid organ transplantation, IL-1 inhibition in addition to standard immunosuppressive regimens may dampen inflammation and protect against negative graft outcome.…”
Section: Multifactorial Inflammatory Conditionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies identified associations between levels of IL-1β and IL-1Ra in serum and urine and negative graft outcome; studies in experimental animals and observations in humans also substantiated a possible protective effect of blocking IL-1 after solid organ transplantation (reviewed in Mulders-Manders et al, 2017 ). New evidence suggests that in patients undergoing solid organ transplantation, IL-1 inhibition in addition to standard immunosuppressive regimens may dampen inflammation and protect against negative graft outcome.…”
Section: Multifactorial Inflammatory Conditionsmentioning
confidence: 93%
“…Three patients undergoing renal transplantation were receiving treatment with anakinra in the peri-operative and post-operative period for underlying IL-1-driven autoinflammatory diseases (AOSD, CAPS, and FMF, respectively). Kidney function increased rapidly in all patients; anakinra was well tolerated and safe with the exception of minor infections ( Mulders-Manders et al, 2017 ). The beneficial effects of treatment are likely due to dampening of ischemia-reperfusion injury, which accompanies renal transplantation and leads to release of IL-1 and to impaired graft function.…”
Section: Multifactorial Inflammatory Conditionsmentioning
confidence: 96%
“…97 Administration of anakinra to a small number of renal transplant patients appears to be safe and efficacious. 98 Besides limited study in kidney transplant recipients with familial Mediterranean fever, 99 canakinumab has yet to be assessed as a diseasemodifying therapy in transplant patients.…”
Section: Inhibition Of Mac Signaling and Pro-inflammatory Effectsmentioning
confidence: 99%
“…antagonists and membrane decoys have been exploited for therapeutics that target IL-1 cytokine function during rheumatoid arthritis, autoinflammatory disease, cardiovascular disease, restenosis following angioplasty, systemic sclerosis, IRI, and diabetes. 41,44,45 In our IRI model, the natural rat IL-1RA was upregulated at POD3, but this is likely too late to prevent immune-mediated damage. However, Anakinra presents a prime candidate for clinical intervention by targeting IRI early inflammatory processes.…”
Section: Discussionmentioning
confidence: 92%
“…Natural mechanisms limit IL‐1‐induced immunopathogenesis and promote adaptive immunity and wound healing. Soluble IL‐1R antagonists and membrane decoys have been exploited for therapeutics that target IL‐1 cytokine function during rheumatoid arthritis, autoinflammatory disease, cardiovascular disease, restenosis following angioplasty, systemic sclerosis, IRI, and diabetes 41,44,45 . In our IRI model, the natural rat IL‐1RA was upregulated at POD3, but this is likely too late to prevent immune‐mediated damage.…”
Section: Discussionmentioning
confidence: 99%